KESALAHAN PENGGUNAAN ADVERBIA再 ZÀI DAN又 YÒU PADA MAHASISWA PROGRAM STUDI BAHASA DAN BUDAYA TIONGKOK FAKULTAS ILMU BUDAYA UNIVERSITAS PADJADJARAN - TRI BIGRIT CLEVERESTY; URAY AFRINA (Direktorat Pendidikan dan Internasionalisasi, 2022)
This research aimed to determine the misuse of the adverbs再 zài and 又yòu on the Chinese Language and Culture at Faculty of Cultural Science Universitas Padjadjaran. Chinese language learners. This research applied qualitative approach with data collection techniques using the test techniques through test instruments. Result shows that the error rate of using the adverbs再 zài and 又yòu reached 30%,with four types of errors; omission ,addition, misselection and misordering. The factors that influenced these misuse are: the interlingual factor or the factor from the mother tongue, the intralingual factor from the students' understanding levels and students' vocabulary mastery, and the last factor is the performance error factor.